2022
DOI: 10.3390/toxics10050208
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Coupled with a High-Fat Diet Promotes Hepatosteatosis through Reactive-Oxygen-Species-Induced CD36 Overexpression

Abstract: Bisphenol A (BPA) is an endocrine-disrupting chemical that affects lipid metabolism and contributes to non-alcoholic fatty liver disease (NAFLD). The mechanism of BPA exposure in hepatic lipid accumulation and its potential effect on NAFLD remain unclear. This study investigated the effect of BPA-exposure-induced hepatic lipid deposition on the pathology of NAFLD and its underlying mechanism in vitro and in vivo. BPA increased intracellular reactive oxygen species (ROS) levels, and promoted fatty acid uptake t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
6
7
0
Order By: Relevance
“…1). In accordance with our data, an increase in serum TG levels by combined exposure to HF and BPA has been reported earlier, and previous studies have reported BPA-ampli ed promotion of fatty liver by enhancing reactive oxygen species production and hepatic lipid accumulation (Lee et al 2022, Pirozzi et al 2020). Activation of ER stress is a key pathological mechanism of steatosis (Zhang et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1). In accordance with our data, an increase in serum TG levels by combined exposure to HF and BPA has been reported earlier, and previous studies have reported BPA-ampli ed promotion of fatty liver by enhancing reactive oxygen species production and hepatic lipid accumulation (Lee et al 2022, Pirozzi et al 2020). Activation of ER stress is a key pathological mechanism of steatosis (Zhang et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that BPA may exert toxicity by inhibiting body weight gain. This result agrees with the results of a previous study in which 8-week-old HF/ high-cholesterol/high-cholic acid diet (HFCCD)-fed C57BL/6 male mice were treated with 50 mg/kg/day BPA for 8 weeks (Lee et al 2022). BPA coupled with HFCCD promoted the development of fatty liver by enhancing reactive oxygen species production in hepatocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Wada et al [ 205 ] showed that BPA and 4-NP exposure stimulated lipid accumulation in Huh-7 cells. Similarly, Lee et al [ 206 ] confirmed that BPA increased intracellular lipid accumulation and fatty acid uptake in Huh-7 cells.…”
Section: Hepatic Cellular Modelsmentioning
confidence: 80%
“…Another study further explored that at very low doses of BPA can induces prostate cancer cells migration [ 91 ], and similar effects were observed in breast cancer cells [ 92 , 93 ]. However, the link between BPA and CD36 expression has been determined in non-alcoholic fatty liver disease (NAFLD), which BPA increases hepatic lipid uptake by stimulating ROS-induced CD36 overexpression [ 94 ]. Based on this evidence, further studies must be investigated to understand the underlying mechanism and association of BPA with CD36 in cancer progression and immune response.…”
Section: Involvement Of Cd36 and Macrophages In Metastasismentioning
confidence: 99%